Sustainable Mobility in Europe: the Role of Participation at the Neighbourhood Scale - Maltese, Ila; Mariotti, Ilaria (TeMA - Journal of Land Use, Mobility and Environment, 2011)
In the last decades, many projects of urban development, following the principles of sustainability, have been realized in Europe. Specifically, it has been demonstrated that sustainable strategies can have significant results if they are carried on at neighbourhood level. When adopting a SM strategy, a large number of stakeholders is affected by its impacts and many conflicts could easily arise. Therefore, participation plays a crucial role, firstly, because it is the most effective means to gain, deliver and sustain benefits deriving i.e. from SM interventions; secondly because some tendency for individuals is proved in adjusting their preferences to the average of the social group they belong to, thus sparking off a virtuous circle towards SM. Within this context, the present paper analyses a panel of 37 European neighbourhoods, which are considered best practices for sustainability, in order to evaluate their SM strategies, and specifically investigate the role played by participation and collective actions in enhancing and achieving SM. To do so, specific SM strategies and related indicators have been identified, according to two previous papers written by the authors (Maltese et al., 2011; Bolchi et al., 2011), and an empirical investigation on the SM strategies is presented. In particular, the empirical analysis underlines the role played by participation in enhancing SM and the commonalities and differences among the neighbourhoods.